2018
DOI: 10.1111/nyas.13927
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical cyclones over the oceanic basins: a review

Abstract: Subtropical cyclones are hybrid systems presenting a warm core at low levels, as tropical cyclones, and a cold core at upper levels, as extratropical cyclones. Their genesis can be as proper subtropical system or from the transitions (extratropical to subtropical or tropical to subtropical). Subtropical cyclones occur mostly over the sea and generate intense near surface winds with great impacts on human activities and ecosystems. We present a review of the main features, as obtained from observations and nume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 91 publications
1
32
0
1
Order By: Relevance
“…Subtropical cyclones occur in most ocean basins, and their thermal structure is characterized by a warm core at low levels and a cold core at upper levels (e.g., see [125] for a comprehensive review). While their genesis occurs in the subtropics, the cyclones can propagate into the midlatitudes [126].…”
Section: Subtropical Cyclonesmentioning
confidence: 99%
“…Subtropical cyclones occur in most ocean basins, and their thermal structure is characterized by a warm core at low levels and a cold core at upper levels (e.g., see [125] for a comprehensive review). While their genesis occurs in the subtropics, the cyclones can propagate into the midlatitudes [126].…”
Section: Subtropical Cyclonesmentioning
confidence: 99%
“…They are frequently referred to as medicanes (MEDIterranean hurriCANES [2]) due to their resemblance to tropical cyclones. Recently, Fita and Flaounas [3] studied the medicane of December 2005 and suggested that TLCs are hybrid systems, which may exhibit features of both tropical and extratropical cyclones, and can be classified as part of the wider category of subtropical cyclones [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although subtropical cyclones have been mentioned in the literature since the 1960s (e.g., Reference [7]), greater attention to these systems only occurred after Reference [4] had developed the Cyclone Phase Space (CPS) methodology to classify cyclone types. The CPS application has contributed to the identification of subtropical cyclones over different oceanic basins, as synthesized by Reference [8], and with this information some studies have investigated their precursors. According to the References [6,[8][9][10][11][12][13], the genesis of the subtropical cyclones is generally associated with a weak cyclonic anomaly at the surface, which is dynamically supported by the presence of a trough or cut-off low at the mid-upper levels of the troposphere.…”
Section: Introductionmentioning
confidence: 99%